2022
DOI: 10.3390/ijms24010597
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Staphylococcus aureus in the Specific Context of Cystic Fibrosis

Abstract: Staphylococcus aureus is a major human pathogen whose characteristics support its success in various clinical settings including Cystic Fibrosis (CF). In CF, S. aureus is indeed the most commonly identified opportunistic pathogen in children and the overall population. S. aureus colonization/infection, either by methicillin-susceptible or methicillin-resistant strains, will become chronic in about one third of CF patients. The persistence of S. aureus in CF patients’ lungs, despite various eradication strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 146 publications
0
6
0
1
Order By: Relevance
“…At a 1% v/v concentration, the essential oils (EOs) extracted from Piper nigrum and Mentha suaveolens were found to diminish Staphylococcus aureus biofilm development by 40%, mainly by decomposing EPS and dismantling the surface, as demonstrated by scanning electron microscopy (SEM), but not by inhibiting bacterial growth. Eugenol and β-caryophellene were found to be responsible for the anti-biofilm effect [ 118 ]. Table 2 presents details of the efficacy of the tested plant extracts against well-known biofilm-forming bacteria.…”
Section: Methods Of Combating Biofilmsmentioning
confidence: 99%
“…At a 1% v/v concentration, the essential oils (EOs) extracted from Piper nigrum and Mentha suaveolens were found to diminish Staphylococcus aureus biofilm development by 40%, mainly by decomposing EPS and dismantling the surface, as demonstrated by scanning electron microscopy (SEM), but not by inhibiting bacterial growth. Eugenol and β-caryophellene were found to be responsible for the anti-biofilm effect [ 118 ]. Table 2 presents details of the efficacy of the tested plant extracts against well-known biofilm-forming bacteria.…”
Section: Methods Of Combating Biofilmsmentioning
confidence: 99%
“…We have selected cystic fibrosis and obesity as our case study, and we have validated the top 10 microbes in the PubMed database that rank in the prediction of these two diseases, both of which have an accuracy of 90%, and Table 2 shows the prediction results for cystic fibrosis ( CF ). CF is an inherited exocrine gland disease that primarily affects the gastrointestinal and respiratory systems and can lead to bronchitis, malnutrition, and other symptoms, and it is estimated that there are about 70,000 cases worldwide, with approximately 1,000 new cases added each year ( Jean-Pierre et al, 2023 ). According to previous studies, a relationship exists between CF and S. aureus , and Jean-Pierre et al (2023) concluded that S. aureus is the main opportunistic pathogen in CF patients and that biofilm production is a determining factor for CF patients to have persistent episodes of S. aureus respiratory infections.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, cell-cell adhesion systems evolve to match the needed kinetics and the duration of cell-cell binding. Among microbes, cell adhesion can last seconds to minutes to entire lifetimes (especially for cells in persistent biofilms and in lichens) [15,27,28]. The requirements for temporary or permanent contacts are achieved through variations in dissociation rates and in avidity.…”
Section: Time and Adhesin Activitymentioning
confidence: 99%